Effect of Replacing Soybean Mean with Maggots on the Diet of Growing Pigs (Global Journal of Science Frontier Research, 2014)
A 92 days feeding trial was conducted with 36 growing Pigs to evaluate the effect of replacing soybean mean with maggots in their diet. The Pigs were randomly allocated to three treatments groups in a complete randomizes design. Each treatment was replicated four times having three Pigs per replicate. Three experimental diets were formulated in which soybean meal was progressively replaced with maggots at 0%, 50%, and 100% and identified as T 1 , T 2 , and T 3 respectively. T 1 served as the control diet. Each of the diets was offered ad libitum to the Pigs. Parameters measured included, weight gain, feed conversion ratio, The result showed a non significant (P > 0.05) difference in all the parameters measured among treatments. Thus the inclusion of maggots in diets up to 100% had no adverse effect on the performance, and carcass characteristics of the animal. Result also showed that replacement of soy bean with yam maggot meal caused a significant (P < 0.05) reduction in the cost of feed/kg weight gain of pigs.